Parenting style and Chinese preschool children’s pre-academic skills: A moderated mediation model of approaches to learning and family socioeconomic status - Xia, Xiaoying (Frontiers in Psychology, 2023)
This study examined the mediating role of children’s approaches to learning (ATL) in parenting style and Chinese preschoolers’ pre-academic skills (i.e. literacy and numeracy) as well as the moderating role of family socioeconomic status (SES) in the mediating process. Participants were 307 children aged five to six years old from four public kindergartens in Shanghai, China. Parents provided demographic information and reported their parenting style (i.e. authoritative, authoritarian, and permissive) and teachers rated each child’s ATL and pre-academic skills. Results indicated that: (1) authoritative parenting positively related to children’s pre-academic skills while no significant relationships were identified either for authoritarian or permissive parenting with pre-academic skills; (2) children’s ATL partially mediated the relationship between authoritative parenting and children’s pre-academic skills; (3) family SES moderated the relationship between children’s ATL and pre-academic skills. Specifically, children’s ATL was more strongly related to pre-academic skills for children from low SES families as compared to their high-SES peers. These findings contribute to the understanding of parenting styles on Chinese children’s early academic achievement and underscore the importance of ATL to children’s pre-academic skills, especially for low-SES children.